1977
DOI: 10.1145/359605.359610
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of the utility of detailed flowcharts in programming

Abstract: This paper describes previous research on flowcharts and a series of controlled experiments to test the utility of detailed flowcharts as an aid to program composition, comprehension, debugging, and modification. No statistically significant difference between flowchart and nonflowchart groups has been shown, thereby calling into question the utility of detailed flowcharting. A program of further research is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(59 citation statements)
references
References 9 publications
2
54
2
1
Order By: Relevance
“…Despite the early establishment of a tradition of studying software developers, relatively few studies have examined performance on software maintenance tasks. Prior maintenance research has considered the impact of various factors on maintainers' ability to modify software including program structure (Boehm-Davis et al 1992;Daly et al 1996;Prechelt et al 2001;Sheppard et al 1979;Shneiderman et al 1977), the use of different documentation formats (Curtis et al 1989;Prechelt et al 2002), and the cognitive processes used by software maintainers (Littman et al 1986). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the early establishment of a tradition of studying software developers, relatively few studies have examined performance on software maintenance tasks. Prior maintenance research has considered the impact of various factors on maintainers' ability to modify software including program structure (Boehm-Davis et al 1992;Daly et al 1996;Prechelt et al 2001;Sheppard et al 1979;Shneiderman et al 1977), the use of different documentation formats (Curtis et al 1989;Prechelt et al 2002), and the cognitive processes used by software maintainers (Littman et al 1986). …”
Section: Introductionmentioning
confidence: 99%
“…Further, studies that have examined both comprehension and modification per se have done so in separate experiments rather than in a single experiment that would allow researchers to determine interrelationships (see, for example, Curtis et al 1989;Sheppard et al 1979;Shneiderman et al 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Dolado [5] has shown that some modern data mining estimation methods are not better than classical regression. -Shneiderman et al experiment [24] on the same analysed whether an algorithm is easier to comprehend if presented as a flow chart or as a pseudo code. Authors concluded that there is no difference between both.…”
Section: Some Epistemological Results Of the Empirical Research Appromentioning
confidence: 99%
“…This suggests investigation mf the properties of various techniques for expressing a program's structure. While some work has already been done on the merits of flowcharts, (e.g., Ramsey, Atwood, and Van Doren, 1978;Shneiderman, Mayer, McKay, and Heller, 1977), this line of research needs to be expanded. A useful focus would be on the relationship between the effectiveness o the communication technique used and the characteristics of the program.…”
Section: General Conclusionmentioning
confidence: 99%